Maternal and Neonatal Outcomes in Pregnant Women with Hemoglobin E: A Cross Sectional Study - A, Rathna; Sharma, Nidhi (Journal of Neonatal Surgery, 2025)
Background: Hemoglobin E (HbE) is a prevalent hemoglobin variant in Southeast Asia. While HbE trait is often asymptomatic, HbE disease and HbE/β-thalassemia can cause clinically significant anemia, particularly during pregnancy. Despite its prevalence, the impact of HbE on maternal and fetal outcomes remains under-researched. Methods: A hospital-based cross-sectional study was conducted at Saveetha Medical College among 355 pregnant women. Hemoglobin variants were identified via HPLC. Maternal characteristics, laboratory values, and pregnancy outcomes were recorded. Statistical analyses included chi-square tests and multivariate regression. Results: HbE variants were present in 27.9% of participants: 22.0% had HbE trait, 3.4% had HbE disease, and 2.5% had HbE/β-thalassemia. Women with HbE variants, particularly HbE disease and HbE/β-thalassemia, had significantly higher rates of severe anemia (41.7–55.6%), blood transfusions (25–33.3%), and preterm births (25–33.3%). Early screening and management reduced complications significantly: severe anemia (8.9% vs. 38.9%), preterm birth (11.1% vs. 29.6%), and NICU admissions (6.7% vs. 22.2%). Conclusions: HbE disorders significantly impact pregnancy outcomes, even in heterozygous states. Early screening and risk-based management can dramatically improve maternal and neonatal outcomes. These findings advocate for the integration of routine HbE screening into prenatal care in high-prevalence regions to inform targeted interventions and public health policies.